Corticosteroid injection plus exercise versus exercise, beyond advice and a heel cup for patients with plantar fasciopathy: protocol for a randomised clinical superiority trial (the FIX-Heel trial) - Henrik Riel; Bill Vicenzino; Jens Lykkegaard Olesen; Martin Bach Jensen; Lars Holger Ehlers; Michael Skovdal Rathleff (Trials, 2020)
Abstract Background Plantar fasciopathy has a lifetime prevalence of 10%. Patients experience sharp pain under the heel, often for several months or years. Multiple treatments are available, but no single treatment appears superior to the others. A corticosteroid injection offers short-term pain relief but is no better than placebo in the longer term (> 8 weeks). Heavy-slow resistance training has shown potentially positive effects on long-term outcomes (> 3 months), and combining exercises with an injection may prove to be superior to exercises alone. However, the effect of heavy-slow resistance training compared with a simpler approach of patient advice (e.g., load management) and insoles is currently unknown. This trial compares the efficacy of patient advice with patient advice plus heavy-slow resistance training and with patient advice plus heavy-slow resistance training plus a corticosteroid injection in improving the Foot Health Status Questionnaire pain score after 12 weeks in patients with plantar fasciopathy. Methods In this randomised superiority trial, we will recruit 180 patients with ultrasound-confirmed plantar fasciopathy and randomly allocate them to one of three groups: (1) patient advice and an insole (n = 60); (2) patient advice, an insole, and self-dosed heavy-slow resistance training consisting of heel raises (n = 60); or (3) patient advice, an insole, heavy-slow resistance training, and an ultrasound-guided corticosteroid injection (n = 60). All participants will be followed for 1 year, with the 12-week follow-up considered the primary endpoint. The primary outcome is the Foot Health Status questionnaire pain domain score. Secondary outcomes include the remaining three domains of the Foot Health Status Questionnaire, a 7-point Global Rating of Change, the Pain Self-Efficacy Questionnaire, physical activity level, health-related quality of life measured by the EQ-5D-5L, and Patient Acceptable Symptom State, which is the point at which participants feel no further need for treatment. Additionally, a health economic evaluation of the treatments will be carried out. Discussion This trial will test if adding heavy-slow resistance training to fundamental patient advice and an insole improves outcomes and if a corticosteroid injection adds even further to that effect in patients with plantar fasciopathy. Trial registration ClinicalTrials.gov, NCT03804008. Prospectively registered on January 15, 2019.